Increased Water Diffusion in the Parcellated Cortical Regions from the Patients with Amnestic Mild Cognitive Impairment and Alzheimer's Disease - Lin, Sung-Han; Hsu, Wen-Chuin; Ng, Shu-Hang; Cheng, Jur-Shan; Khegai, Oleksandr; Huang, Chin-Chang; Chen, Yao-Liang; Chen, Yi-Chun; Wang, Jiun-Jie (Frontiers in Aging Neuroscience, 2017)
Background The loss of cortical neuron environment integrity is the hallmark of neurodegeneration diseases such as Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI). To reveal the microenvironment changes in cerebral cortex, the current study aimed to examine the changes of mean diffusivity (MD) in parcellated brain among AD, aMCI patients and normal controls (NC). Methods Diffusion tensor imaging data with the whole brain coverage were acquired from 28 AD (aged 69.4±8.2 year old), 41 aMCI patients (aged 68.2±6.4 year old) and 40 NC subjects (aged 65.7±6.4 year old). Subsequently, the MD values were parcellated according to the standard automatic anatomic labeling (AAL) template. Only the 90 regions located in the cerebral cortex were used in the final analysis. The mean values of MD from each brain region were extracted and compared among the participant groups. The integrity of the white matter tracts and gray matter atrophy was analyzed using the track-based spatial statistics and voxel-based morphometry approaches, respectively. Results Significant differences of MD were noticed both in aMCI and AD patients, in terms of the affected regions and the amount of increase. The hippocampus, parahippocampal gyrus and cingulum were the most significantly affected regions in AD patients. From all the 90 cerebral cortex regions, significant increase of MD in the AD patients was found in 40 regions, compared to only one (fusiform gyrus on the right) in aMCI patients. In the disease affected regions, the MD from aMCI patients is in state between NC and AD patients. Conclusions Increased MD in the specific regions of the brain shows the feasibility of MD as an indicator of the early stage cortical degeneration in aMCI and AD patients.